Raising Children: Philosophical Hermeneutics and Children with Life-Limiting Illness - Katherine Wong (University of Calgary, 2019)
Children are authentically hermeneutic beings; they are not only open to the possibility that the other may be right, but often expect that the perspective of the other is correct. The hermeneutic tenets of history, tradition, and authority shape how children and childrearing are perceived in society. Children are often regarded as in-progress, and this has implications for children diagnosed with life-limiting illness and the pediatric palliative healthcare providers that care for them. Children who experience unique phenomena, such as dying in childhood, may possess an authority gained through superior insight that adults often overlook. Art is a common language that can be used in hermeneutic research to better understand children’s experiences of life-limiting illness. Researchers who work with children must raise the value of children’s perspectives, find a shared language to foster understanding, and enter the circle with the same genuine hermeneutic spirit that children exemplify.